2006
DOI: 10.3354/dao069053
|View full text |Cite
|
Sign up to set email alerts
|

Colony versus population variation in susceptibility and resistance to dark spot syndrome in the Caribbean coral Siderastrea siderea

Abstract: Scleractinian corals appear to be increasingly susceptible to pathogenic diseases, yet it is poorly understood why certain individuals, populations or species are more susceptible to diseases than others. Clearly an understanding of mechanisms of disease resistance in corals is essential to our understanding of patterns of disease incidence and virulence; this work must begin by examining the colony and population levels of organization. The Caribbean coral Siderastrea siderea exhibits variability in susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 64 publications
(47 reference statements)
2
35
0
Order By: Relevance
“…This susceptibility pattern was similar to findings by Borger (2005) in Dominica, where S. siderea was the only species affected by dark spots disease, and by Gochfeld et al (2006) who also found that dark spots most frequently affects S. siderea. Although these results suggest the potential for degradation within S. siderea, another study by Borger (2003) found that the effects of dark spots disease on the coral community were low compared to the more virulent tissue eroding diseases white plague and black band disease.…”
Section: Discussionsupporting
confidence: 74%
“…This susceptibility pattern was similar to findings by Borger (2005) in Dominica, where S. siderea was the only species affected by dark spots disease, and by Gochfeld et al (2006) who also found that dark spots most frequently affects S. siderea. Although these results suggest the potential for degradation within S. siderea, another study by Borger (2003) found that the effects of dark spots disease on the coral community were low compared to the more virulent tissue eroding diseases white plague and black band disease.…”
Section: Discussionsupporting
confidence: 74%
“…As such, MWS also has the potential to shift the coral community structure of the reefs within Kaneohe Bay towards coral species that are not susceptible to this disease. Differential disease susceptibility among coral genera has been found in a number of studies (Willis et al 2004, Gochfeld et al 2006, Aeby 2007, Vargas-Angel 2009, and individual coral dis-eases show variability in host specificity. For example, BBD has low host specificity and affects 19 Caribbean shallow-water coral species and 45 Indo-Pacific coral species (Sutherland et al 2004), whereas white band disease only affects Acropora sp.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in types and levels of defense vary among families, genera, and species and even at the level of the individual colony (Mullen et al 2004, Gochfeld et al 2006). These differences might enable particular populations, species, or genotypes to have an advantage over others in resisting invasion by pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Scleractinian corals have also been found to produce chemical defenses, although these are less well studied than those in soft-bodied invertebrates. Gochfeld (1997) demonstrated chemical defenses against predatory fish in 2 species of Hawaiian corals, and in one of the earliest studies on coral chemical defenses, Gunthorpe & Cameron (1990) documented antibacterial activity in 37 of 55 species of Australian corals. Likewise, Koh (1997) found that extracts from 100 Australian coral species inhibited growth of a marine cyanobacterium, and extracts from 8 species inhibited growth of marine bacteria.…”
Section: Introductionmentioning
confidence: 99%